2008
DOI: 10.1097/ico.0b013e318157a111
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Outcomes of Phototherapeutic Keratectomy in the Developing World

Abstract: PTK is an efficacious treatment modality for symptomatic relief and visual gain in cases with superficial corneal involvement and bullous keratopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 17 publications
2
26
1
3
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18] Several studies have shown encouraging results after PTK in eyes with bullous keratopathy. [4][5][6][7][8] The proposed mechanism of action of PTK in bullous keratopathy is by ablation of the superficial epithelial nerve plexus, ablationrelated reduction of stromal ''osmotic load,'' thereby increasing endothelial efficacy in its dehydrating function and creation of a smooth anterior surface. 5 In a retrospective study on 103 eyes that underwent PTK for bullous keratopathy at our centre, 4 a significant decrease (P , 0.0001) in the number of patients with severe symptoms was noted after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13][14][15][16][17][18] Several studies have shown encouraging results after PTK in eyes with bullous keratopathy. [4][5][6][7][8] The proposed mechanism of action of PTK in bullous keratopathy is by ablation of the superficial epithelial nerve plexus, ablationrelated reduction of stromal ''osmotic load,'' thereby increasing endothelial efficacy in its dehydrating function and creation of a smooth anterior surface. 5 In a retrospective study on 103 eyes that underwent PTK for bullous keratopathy at our centre, 4 a significant decrease (P , 0.0001) in the number of patients with severe symptoms was noted after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms were graded on a fixed response scale (Table 1). 4 Patients with a category score of .2 were considered for PTK or AMT, and eligible patients were randomized into 2 groups using randomization charts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report from a tertiary eye care center in India confirmed PTK as an efficacious treatment modality for symptomatic relief and visual gain in cases with superficial corneal involvement and bullous keratopathy [16 ]. This is a retrospective study of 203 consecutive eyes of 191 patients who underwent PTK in the Rajendra Prasad Centre for Ophthalmic sciences in New Delhi with 6-month follow-up.…”
Section: Elevated Corneal Lesionsmentioning
confidence: 91%
“…Die Laserchirurgie als primärer abtragender Eingriff [13,41] dürfte aber nur für kleine Knötchen geeignet sein. Massive Aufwachsungen sollten primär mechanisch entfernt werden, wie es auch über-wiegend Praxis ist.…”
Section: "Stumpfes Abpräparieren" Statt Keratoplastikenunclassified